Prospects of Nanotechnology in Bangladesh Perspective (Journal of Chemical Engineering, 2017)
Nanotechnology brings huge promise in the research and development in industrial sectors to increase the efficiency and productivity. It deals with matters at as small as billionth of a meter scale. At this nano scale, the physiochemical properties of matter dramatically change due to quantum confinement. So there are huge possibilities in developing applications by harnessing the nano scaled physiochemical properties of nano materials in numerous fields. Bangladesh, being a developing country lacks the proper guideline and investment to take advantage of this technology. Nanotechnology has a huge prospect in this country especially in agriculture and garments sector. If applied properly, nanotechnology can boost the economic growth as well as improve the capacity and quality in agriculture, food and other industrial sectors. This paper describes the current status of Nanotech research and development, applications in major industrial sectors, future prospects in the context of Bangladesh. This paper also discusses the safety, risks and challenges associated with nanotech and provide a general guideline and recommendations for the application of nanotechnology in major industrial sectors of Bangladesh.Journal of Chemical Engineering, Vol. 30, No. 1, 2017: 64-68